Assessment of natural crack initiation and its propagation in slow speed bearings - Elforjani, Mohamed; Mba, David (Taylor & Francis, 2009)
Monitoring of bearings is an essential part of most condition monitoring programmes in rotating machinery. This paper demonstrates the use of acoustic emission (AE) measurements to detect, monitor and locate natural defect initiation and propagation in a thrust rolling element bearing. To undertake this task a special purpose test-rig was built that allowed for accelerated natural degradation of a bearing race. It is concluded that sub-surface initiation and subsequent crack propagation can be detected using a range of time and frequency domain analysis techniques on AE's generated from natural degrading bearings. The paper also investigates the source characterisation of AE signals associated with a defective bearing whilst in operation.
Keywords: acoustic emission condition monitoring source location bearing life and natural crack initiation rolling element bearings acoustic-emission identification diagnosis